Post COVID Syndrome or Long COVID: An Overview - Banerjee, Indrajit; Robinson, Jared (Current Overview on Disease and Health Research Vol. 6, 2022)
The global pandemic caused by the SARS-CoV-2 virus has affected every continent worldwide. The novelty of this virus, its mutations and the rapid speed and unprecedented rate at which it has torn through the global community has in turn lead to an innate lack of knowledge and information about the actual disease caused and the severity of the complications associated with COVID-19. The SARS-CoV-2 virus has been infecting individuals since 2019 and now as of 2022 has been circulating for just over 2 years within the global populous. As the number of cases have risen globally over this period (some of which having contracted the virus twice) further endeavours have been undertaken to better understand the pathogenesis and natural progression of the disease. A condition reported in some cases with extended bouts of sickness or symptoms following the initial infection with COVID was labelled “long COVID” towards the earlier phases of the pandemic (in the spring of 2020), but has only recently gained the global media and medical attention due to its affliction of more individuals on a global basis and has thus warranted further investigation. It is clearly evident that a substantial dearth in information surrounding the SARS-CoV-2 virus and its long-term effects exists, as a substantial rise in post COVID symptoms and complications have been reported globally. The objective of this research was to find out the signs and symptoms, treatment, emerging therapies and ongoing clinical trials of Long COVID. Long COVID is described as a persistent, long-term state of poor health following an infection with COVID-19. The effect of Long COVID is multisystemic in nature with a wide array of signs and symptoms. The most commonly reported clinical features of long COVID are: headaches, myalgia, chest pain, rashes, abdominal pain, shortness of breath, palpitations, anosmia, persistent cough, brain fogs, forgetfulness, depression, insomnia, fatigue and anxiety. Currently no definitive treatment against Long COVID has been approved and the mainstay treatment is divided into Symptomatic, Supportive and Rehabilitative treatment with self-monitoring. The crux of the current treatment trends for Long COVID is that of a multidisciplinary approach with a great portion of the treatment implicating the patient to take an active role in their recovery, self-monitoring and treatment of the syndrome. Hyperbaric oxygen therapy (HBOT), Vitamin C as well as the use of adaptogens has shown promising results and is advisable to be added to the treatment regimen of patients to aid in decreasing fatigue in patients suffering from post-COVID syndrome. The use of melatonin in patients suffering from insomnia and poor sleep hygiene is also advisable. Currently numerous pharmacotherapeutic agents ranging from Montelukast, Deupirfenidone, Nicotinamide riboside, Leronlimab, Adaptogens, Tocilizumab, Probiotics to HBOT are undergoing clinical trials. It is thus with hopeful expectancy that these drug trials will yield a viable definitive treatment for Long COVID.